Underwater concreting and repair - McLeish, Andrew, 1950- (J. Wiley, 1994)
Presents techniques of applying and repairing concrete in freshwater and marine environments for the practicing engineer. Covers materials, inspection, defect evaluation, repair methods, and factors influencing long-term durability of concrete underwater. Includes numerous diagrams and photos. Enables engineers to identify and overcome the many problems associated with concreting in both fresh and sea water. Focuses on the major factors influencing long term durability of concrete in the underwater environment. Discusses inspection, evaluation of defects and methods of repair for existing underwater structures. --